Real-world assessment of the effectiveness of posaconazole for the prophylaxis and treatment of invasive fungal infections in hematological patients: A retrospective observational study. Issue 30 (30th July 2021) - Chen, Xiaochen; Wang, Jianxiang; Wang, Sanbin; Jin, Jie; Li, Junmin; Gao, Sujun; Li, Jianyong; Li, Juan; Liu, Qifa; Hu, Yu; Lin, Dongjun; Sun, Zimin; et al.
Abstract : Abstract: The aim of the study was to analyze the efficacy of posaconazole for the prophylaxis and treatment of invasive fungal diseases (IFDs) in patients with hematological malignancies. In this retrospective observational multi-center study, 762 patients from 25 Chinese hematological centers were enrolled. Inclusion criteria were patients with hematological malignancy or they had undergone hematopoietic stem cell transplantation and received at least 1 dose of posaconazole. The primary endpoints were the observation of breakthrough rates and the clinical efficacy of posaconazole prophylaxis. The secondary endpoint was the efficacy of posaconazole for the treatment of IFDs. Of the 762 enrolled patients, 456 (59.8%) were prescribed posaconazole prophylactically while 243 (31.9%) received posaconazole as an IFD treatment (12 proven, 61 probable, 109 possible, and 61 unclassified IFD cases) for ≥7 days. The overall IFD breakthrough rate (probable cases) for the ≥4 days prophylactic treatment (n = 445) group was 1.6% (95% Cl: 0.6%–3.2%), with breakthrough rates of 2.6% for acute myeloid leukemia/myelodysplastic syndrome patients undergoing chemotherapy and 2.2% for hematopoietic stem cell transplantation patients. For primary antifungal prophylaxis, the breakthrough rate was 1.9% and for secondary antifungal prophylaxis 0%. The overall effective IFD remission rate of patients treated for ≥7 days with posaconazole was 56.0% and the effective remission rate of proven/probable/possible IFD cases was 59.3%. The effective remission rate of posaconazole as salvage therapy was 50% (95% CI: 32.4%–67.6%) including 75% (CI: 19.4%–99.4%) for Aspergillus infections. The present retrospective study confirmed posaconazole as IFD prophylaxis and medication for hematological malignancy patients undergoing various treatments in China. Abstract : Supplemental Digital Content is available in the text